The INFLUENCE OF FRAUD PENTAGON IN DETECTING FRAUDULENT FINANCIAL STATEMENTS - Ananda, Ocha; Rahayu, Sri; Yustien, Reni; Dewi, Erwita (Journal of Business Studies and Management Review, 2024)
This study aims to examine the elements of the Fraud Pentagon proxied by five variables consisting of Pressure (External Pressure), Opportunity (Ineffective Monitoring), Rationalization (Change in Auditor), Ability (Change in Directors), and Arrogance (Frequent Number of CEO's Pictures) which are hypothesized to affect Financial Statement Fraud. The population in this study are Transportation & Logistics sector companies listed on the Indonesia Stock Exchange for the period 2020-2022. The sample in this study was selected using a purposive sampling technique and obtained a sample of 75 observation data. The analysis method in this study uses multiple linear regression which is processed using SPSS 25 software. The results showed that External Pressure affected Financial Statement Fraud. While Ineffective Monitoring, Change in Auditor, Change in Directors, and Frequent Number of CEO Pictures do not affect Financial Statement Fraud.